Phenolic compounds and bioactive properties of Ruscus aculeatus L. (asparagaceae): the pharmacological potential of an underexploited subshrub - Rodrigues, Joana P.B. (2021)
Ruscus aculeatus L. is a subshrub used in traditional medicine in different parts of the world, namely in Europe and the Iberian Peninsula. According to reported folk knowledge, the aerial parts are mainly used as diuretics and the underground organs are used for the treatment of disorders of the urinary system and as a laxative. In this work, the aerial part and the roots and rhizomes of R. aculeatus were chemically characterized with regard to the content of phenolic compounds and bioactive properties. Aqueous (infusions and decoctions) preparations and hydroethanolic extracts from the two mentioned parts of the plant were prepared. Nine phenolic compounds were detected in all the extracts. Apigenin-C-hexoside-C-pentoside isomer II was the major compound in aqueous extracts and, in the hydroethanolic extract was quercetin-O-deoxyhexoside-hexoside followed by apigenin-C-hexoside-C-pentoside isomer II. All extracts revealed antioxidant activity and potential to inhibit some of the assayed bacteria; aqueous extracts of the aerial part and infusions of roots and rhizomes did not show cytotoxic effects on a non-tumor primary cell culture. This preliminary study provides suggestions of the biological potential associated with the empirical uses and knowledge of this species, in particular its bioactivities.